2016
DOI: 10.1063/1674-0068/29/cjcp1507156
|View full text |Cite
|
Sign up to set email alerts
|

Incorporation of Reactive Corrosion Inhibitor in Waterborne Acrylic Polyurethane Coatings and Evaluation of its Corrosion Performance

Abstract: Hydroxyl-epoxy phosphate (HEP) as a reactive corrosion inhibitor was innovatively synthesized by the reaction of bisphenol A epoxy resin with phosphoric acid. HEP was mixed with hydroxyl acrylate resin, and crosslinked with waterborne isocyanate curing agent, which was used to form waterborne HEP/acrylic polyurethane composite (HEP-APU) coatings on Q235 steel surfaces. Electrochemical impedance spectroscopy and polarization curves were applied to analyze the corrosion behavior of the HEP-APU coatings in 3.5wt%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…66 as shown in Figure 9B, the phosphate in the coating can react with the hydroxyl groups in the substrate to form a dense phosphate protective film, which can effectively prevent the lateral diffusion of the corrosive medium. 51 Therefore, modification of fluorine and phosphate monomers can more effectively enhance the corrosion resistance of the coating.…”
Section: Anti-corrosion Mechanism Of Modified Resinmentioning
confidence: 99%
See 1 more Smart Citation
“…66 as shown in Figure 9B, the phosphate in the coating can react with the hydroxyl groups in the substrate to form a dense phosphate protective film, which can effectively prevent the lateral diffusion of the corrosive medium. 51 Therefore, modification of fluorine and phosphate monomers can more effectively enhance the corrosion resistance of the coating.…”
Section: Anti-corrosion Mechanism Of Modified Resinmentioning
confidence: 99%
“…49,50 Therefore, phosphate is introduced into the coating, which can prevent water molecules from contacting the metal to achieve the purpose of rust prevention. For example, Gu et al 51 synthesized a phosphate corrosion inhibitor with bisphenol A epoxy resin and phosphate and incorporated it into acrylic resin. The results show that the adhesion and corrosion resistance of the coating are greatly improved by the introduction of phosphate.…”
Section: Introductionmentioning
confidence: 99%
“…It was found that the presence of a dense film of phosphating group, implies that it can act as a corrosion inhibitor [51,52]. By using this characteristic of phosphate groups Chetan et al have developed phosphorylated polyvinyl alcohol doped with polyaniline nanoparticles as a potential anticorrosion coating [53].…”
Section: Polymer Incorporated Water-based Epoxy Coatingsmentioning
confidence: 99%
“…However, traditional coatings with epoxy resin are organic solvent based, involving large amounts of volatile organic compounds, which either lead to severe environmental pollution or require a high-cost recovery system. Therefore, it is highly desired to replace solvent based epoxy resins with waterborne ones for coating applications. , However, coatings with waterborne epoxy resins (WER) suffer unsatisfactory barrier properties against permeation of water, oxygen, and corrosion ions, because certain amounts of hydrophilic groups and surfactants remain in the film structure …”
Section: Introductionmentioning
confidence: 99%
“…14,15 However, coatings with waterborne epoxy resins (WER) suffer unsatisfactory barrier properties against permeation of water, oxygen, and corrosion ions, because certain amounts of hydrophilic groups and surfactants remain in the film structure. 16 Incorporation of two-dimensional plate-like nanofillers can effectively promote the mechanical and barrier properties of organic coating films. Hitherto, various studies have proven that nanofillers such as graphene oxide (GO), 17,18 montmorillonoid, 19,20 hexagonal boron nitride (h-BN), 21,22 and molybdenum disulfide (MoS 2 ) 23 can improve the anticorrosion performance of a coating film.…”
Section: Introductionmentioning
confidence: 99%